Hubungan Pengetahuan, Sikap dan Budaya Akseptor KB Memilih AKDR di Desa Bebesen Kecamatan Bebesen Kabupaten Aceh Tengah 2025 - Rahmah Rahmah; Dede Dessy Listyana; Raodah Raodah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
The new paradigm in the National Family Planning program has changed its vision, which was originally aimed at realizing the norm of a Small Happy Prosperous Family (NKKBS), to a vision of achieving Quality Families. One of the efforts in the family planning program is the regulation of pregnancy spacing through the use of contraceptive devices, which are tools used to prevent pregnancy. This study aims to determine the relationship between the knowledge, attitudes, and culture of family planning acceptors and the selection of Intrauterine Contraceptive Devices (IUCD) in Bebesen Village, Bebesen District, Central Aceh Regency in 2025. This research is descriptive-analytic with a cross-sectional approach and uses purposive sampling method with 59 respondents. The study was conducted from January 12 to February 25, 2025. Statistical analysis using the chi-square test shows a P-value of 0.016, indicating a relationship between knowledge and the selection of IUCD. Further analysis using the chi-square test shows a P-value of 0.013, indicating a relationship between the attitudes of family planning acceptors and the selection of IUCD, and the statistical analysis with the chi-square test shows a P-value of 0.030, indicating a relationship between the culture of family planning acceptors and not selecting IUCD.